How Can Malaysian Public Universities Make The Most of Their Campus Real Estate? – A Conceptual Framework for Managing Corporate Real Estate - Bakhir, Azmah; Nawawi, Abdul Hadi; Basrah, Noraliza (International Journal of Sustainable Construction Engineering and Technology, 2023)
Most university campus buildings have low occupancy rates and high operating and maintenance costs because they are historically designed to fulfil the needs of specific faculties without any utility value. Real estate resources in universities tend to be undermanaged and misunderstood as overhead costs by top-level management. The problems are prevailing within Malaysian public universities. Therefore, it is critical to take a more integrated corporate real estate management (CREM) approach, which is appropriate for public institutions with limited autonomy and strict regulatory oversight. This paper aims to determine key themes of CRE strategies and critical components of CREM alignment for successful implementation within an organisation. A comprehensive literature review was done on CREM at higher education institutions between 1990 and 2021. Then, a summary of several important publications was provided. The discussion of several approaches for coordinating CRE and organisational strategies followed. Because there is still a disconnect between the theoretical framework and the real-world implementations by educational administrators, the gap in Malaysia concerning CREM past research was then discovered. The article concludes by recommending a conceptual framework for CREM implementation in public universities in Malaysia that incorporates CRE strategies, alignment, and portfolio management. In order to enjoy a stream of revenues and support their core business operations, public universities can integrate CREM knowledge while managing their properties and resources. The conceptual framework promotes the overall effectiveness of investment in Malaysian higher education and offers helpful information for public institutions and government organisations involved in education.